The United States' credibility in a polarized age of politics - Toy, Joshua (My University, 2024)
Political polarization is a growing area of research among political science scholars. This thesis focuses on domestic partisan polarization's effects on the credibility of the United States' foreign policy signaling internationally. Political polarization has increased in the United States since the end of the Cold War, affecting the domestic political process for actors holding or seeking office. The domestic impact of heightened polarization is lower accountability for actors holding or seeking public office. Reduced accountability for Presidents leads to less consistent foreign policies across administrations, which results in the questioning of the United States' commitments by other international actors. Feasible generalized least squares models were used to test the polarization hypotheses quantitatively. Lastly, a qualitative case study covering the Joint Comprehensive Plan of Action (JCPOA) is utilized to illustrate the implications rising polarization has on the credibility of the United States' commitments.
Keywords: Accountability; Audience costs; Credibility; Foreign policy; Hedging; Partisanship; Polarization; Signaling